Building Consumer Buying Interest through Content Marketing and Consumer Engagement - Agra, Belligo; Prakoso, Sajiwo Tri (Management Analysis Journal, 2022)
Content marketing has become the most popular marketing tool in recent years. content marketing can trigger consumer engagement and furthermore can stimulate consumer buying interest. however, there is a bias in previous research. Previous research generally used big brands as the research context. content distributed by big brands loses credibility, because there are questions whether they are viral because of the brand or the content itself. This study tries to fill the gap by examining the effect of satisfaction on small business content on brand trust and purchase intention. This research was conducted in Surakarta and Yogyakarta during the end of 2021. The respondents were Millennials and Gen- z. These two generations have a high intensity on social media so they are considered reliable to fill out the questionnaire. Samples were taken by non-probability sampling method. The type of non-probability sampling technique used is purposive sampling because there are certain criteria that are required in order to fill out the questionnaire in this study. This research is carried out with a quantitative approach because it intends to test the relationship between variables. Data testing was carried out using the SEM-PLS method. PLS was chosen because this study tested a new model. The results of this study indicate that consumer satisfaction with content has an important role in buying interest.